Subjective Evaluation and Attention to individual Aspects of a health-promoting Diet in healthy older People - Siebentritt, Hanna; Kiesswetter, Eva; Hannink, Anne; Brandl, Beate; Skurk, Thomas; Wawro, Nina; Linseisen, Jakob; Hauner, Hans; Volkert, Dorothee (Ernährungsumschau, 2022)
Older people are considered to have a relatively high level of nutritional awareness. However, it is not yet known which importance they attach to individual aspects of a healthy diet. Using standardized questionnaires, 159 healthy seniors (78 ± 3 years, 50% female) were asked about the importance of and attention to 15 nutritional aspects and about their usual food consumption. The recommendation "drinking 1–1.5 liters a day" was rated most frequently as "very important" (69.8%), while "not eating too little" and "eating legumes" were rated least frequently (10.1% each). There was a high level of agreement between rating of importance and attention, with high ratings of importance more common across the board. For most nutritional aspects, ratings of importance or attention were also reflected in reported food intake. The discrepancies identified between rating and attention imply that, in addition to purely imparting knowledge, nutrition education and counseling should also address the possibilities for implementing nutrition aspects in everyday life.<br
CRIS-Team WoS Importer:2022-07-15
Keywords: health-promoting diet; senior citizens; private household; dietary attitudes